WATERSHED PRIORITIZATION ACROSS ERBIL PROVINCE FOR SOIL EROSION MANAGEMENT VIA MORPHOMETRIC ANALYSIS - & Karim, Mohammed (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2020)
Soil erosion is one of the foremost factors giving rise to watershed deterioration due to improper and unwise utilization of natural resources without proper vision, particularly in developing countries like Iraq. Since it is not possible to implement rehabilitation programs over all areas at a time, prioritization plays a major role in identification of the areas which are in need of immediate actions. Accordingly, the current study was conducted to perform morphometric analysis as the basis for prioritization. To achieve the above objective, 30 watersheds of different scales were delineated within Erbil governorate and standard procedures were followed to carry out morphometric analysis. Prioritization ranks were determined for the study watersheds based on computation of compound factors and on the technique for order preference by similarity to ideal solution (TOPSIS). The results indicated that nearly two approaches offered similar results. The regression analysis indicated that the priority rank from (TOPSIS) can be predicted from the priority rank from compound factor computation with a reasonable accuracy. Based on TOPSIS approach, watersheds: Kawlan-smelan, Nawandee, Warte, Prdi-qasre, Nawprdan, Darbandy-rayat, Dargalla and Mergasor fall within the very high priority class and as a consequence immediate actions should be taken to protect these watersheds. By contrast, the watersheds: Kasnazan, Smaquly, Bestana, Kawanyan, Rulka and Degala 1 are categorized under the low prioritization level. Further improvements in specifying the priority ranks can be expected upon coupling land use/land cover with morphometric analysis.